Wspomaganie wyboru wartości rezerwy szkodowej - Wolny, Alicja (Mathematical Model Supporting the Loss Reserve Calculation Process, 2006)
The loss reserves calculation is a very important problem in insurance corporations because this determines the future financial standing. There are many methods of loss reserves calculation proposed by practising insurers and academics it is not easy to say which method is the best one and which should be applied in practice. We propose to consider loss reserves calculation as a multicriteria decision making problem. Such an approach enables to take into consideration the results obtained by various actuarial methods and also individual decision maker's preferences which come from corporation financial standing and market strategy. In the first part of this paper we discuss the loss reserves calculation process as the multi-criteria decision making problem. In the second part the mathematical model supporting this process is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 188-194